2016
DOI: 10.1016/j.camwa.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Randomized LU decomposition using sparse projections

Abstract: A fast algorithm for the approximation of a low rank LU decomposition is presented. In order to achieve a low complexity, the algorithm uses sparse random projections combined with FFTbased random projections. The asymptotic approximation error of the algorithm is analyzed and a theoretical error bound is presented. Finally, numerical examples illustrate that for a similar approximation error, the sparse LU algorithm is faster than recent state-of-the-art methods. The algorithm is completely parallelizable tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…A new algorithm is presented, which yields with high probability, a rank r SVD approximation for an m × n matrix that achieves an asymptotic complexity of O(nnz(A)pk + (m + n)k 2 ). Additionally, we showed that the approximated LU algorithm in [1], which uses sub-Gaussian random matrices, has a computational complexity of O(nnz(A)pk + (m + n)k 2 ). We showed in the experiments that although the derived error bounds are not as tight as the bounds from the algorithms in [3,9], in practice, the algorithm in this paper reaches the same error in less time.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A new algorithm is presented, which yields with high probability, a rank r SVD approximation for an m × n matrix that achieves an asymptotic complexity of O(nnz(A)pk + (m + n)k 2 ). Additionally, we showed that the approximated LU algorithm in [1], which uses sub-Gaussian random matrices, has a computational complexity of O(nnz(A)pk + (m + n)k 2 ). We showed in the experiments that although the derived error bounds are not as tight as the bounds from the algorithms in [3,9], in practice, the algorithm in this paper reaches the same error in less time.…”
Section: Resultsmentioning
confidence: 99%
“…This algorithm does not take advantage of the fact that Ω can be a sparse matrix. Thus, Algorithm 5.1 can be adapted similarly to the algorithm in Theorem 47 [3] and to the LU decomposition algorithm [1]. For SVD approximation to be of rank r, we use the following version of Weyl's inequality: Proof.…”
Section: Approximated Matrix Decompositions 41 Randomized Svd Using mentioning
confidence: 99%
See 3 more Smart Citations